Conversion of Intrathecal Opioids to Fentanyl in Chronic Pain Patients With Implantable Pain Pumps: A Retrospective Study. Issue 7 (6th March 2019) - Kim, David Daewhan; Patel, Ankit; Sibai, Nabil
Abstract : Objectives: Conversion between routes such as intravenous (IV), epidural (EP), and intrathecal (IT) routes for morphine is well established. Conversion ratios for IV:EP:IT fentanyl and conversion from IT morphine/hydromorphone to IT fentanyl have been challenging given the lipophilic nature of fentanyl. Our study reviews the outcomes and conversion ratios reached after converting IT opioids from morphine/hydromorphone to fentanyl in patients with IT pumps. Methods: After Institutional Review Board approval at Henry Ford Health System, a chart review was performed on all patients who had Synchromed II IT pumps implanted 2009–2016 and were converted from morphine/hydromorphone to fentanyl. The chart review included the initial fentanyl dose and fentanyl IV:IT conversion ratio, eventual IT fentanyl dose, and IV:IT conversion ratio reached to give superior VAS from previous IT opioid. Wilcoxon non‐paired signed rank test was used to examine the change in fentanyl dosage and IV:IT conversion ratio. Results: The mean IT morphine equivalent dose at initial conversion was 15.8 mg/day, and the mean fentanyl IT starting dose was 0.73 mg/day (SD = 1.37 mg). The mean fentanyl dose at the end of titration was 0.94 mg/day (SD = 2.05 mg) which represented a significant 25.1% mean dose increase ( P  = 0.004). The initial mean IV:IT fentanyl conversion ratio was 38.7:1 (SD = 33.01), but the mean IV:IT fentanyl conversion ratio at end of titration with better analgesia was significantly lower at 32.9:1 (SD = 27.1) ( P  = 0.016). Conclusions: Given the pharmacokinetics of lipophilic fentanyl compared to hydrophilic morphine/hydromorphone, the current conversion ratio of IV fentanyl to IT fentanyl and IV morphine to IT fentanyl appears to be conservative.